HUBUNGAN PENGETAHUAN, KEBIASAAN MEROKOK DAN PENGGUNAAN APD DENGAN GEJALA GANGGUAN PERNAPASAN PADA PEKERJA SAWMILL DI KELURAHAAN PASIR PANJANG KOTA JAMBI TAHUN 2023 - Zahra Haj Pertiwi; Sugiarto, Sugiarto; Suroso, Suroso (Bajang Institute, 2024)
Occupational diseases are influenced by internal factors such as smoking, not using PPE masks and external factors such as an uncomfortable work environment, dust, temperature effects and so on. This research aims to determine the relationship between knowledge, smoking habits and use of PPE with symptoms of respiratory problems in Sawmill workers in Pasir Panjang Subdistrict, Jambi City in 2023. This type of research is Quantitative with a Cross Sectional approach. The research was conducted at the Sawmill, Pasir Panjang Subdistrict, Jambi City on 5-12 August 2023. The research sample was all 56 Sawmill workers in Pasir Panjang Subdistrict. The data collection method is by interview using a questionnaire. Data were analyzed using the chi square test. The research results showed that 65.5% of respondents experienced symptoms of respiratory problems, 21.8% of respondents had poor knowledge, 43.6% of respondents had a smoking habit and 50.9% of respondents did not use PPE masks. The results of bivariate analysis showed that there was a relationship between smoking habits (p=0.000) and use of PPE (p=0.018) with symptoms of respiratory problems. There was no relationship between knowledge and respiratory symptoms (p=0.808). It is hoped that sawmill owners will increase workers' awareness to carry out health checks at the nearest health center and provide PPE masks for workers